2006
DOI: 10.1007/s10620-006-9428-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of GLUT-1 Overexpression, Tumor Size, and Depth of Invasion with 18F-2-fluoro-2-deoxy-d-glucose Uptake by Positron Emission Tomography in Colorectal Cancer

Abstract: We investigated the wide variability of 18F-2-fluoro-2-deoxy-D: -glucose (FDG) uptake, semiquantified as standardized uptake value (SUV), in positron emission tomography (PET) scanning, in 20 patients with colorectal cancer (CRC), including 1 with synchronous hepatic metastasis. The sensitivity of PET in CRC diagnosis was 100%, with a mean SUV of 8.0 (3.1-11.9). Tumor size and depth of invasion were associated with higher SUVs (P=.0004, .042, respectively). Strong glucose transporter-1 (GLUT-1) expression had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…This process is considered to be mediated by glucose transporters (GLUTs). Among GLUTs, GLUT-1 is one of the most significant mediators of increased glucose influx into cells (3). The rate of glucose transport via GLUT-1 may be altered under conditions in which the metabolic rate must be adjusted, including during cell division (mitosis and meiosis), differentiation, transformation and nutrient starvation (4).…”
Section: Introductionmentioning
confidence: 99%
“…This process is considered to be mediated by glucose transporters (GLUTs). Among GLUTs, GLUT-1 is one of the most significant mediators of increased glucose influx into cells (3). The rate of glucose transport via GLUT-1 may be altered under conditions in which the metabolic rate must be adjusted, including during cell division (mitosis and meiosis), differentiation, transformation and nutrient starvation (4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies are currently conducted as well with regard to the correlation between 18 F-FDG uptake and expression of GLUT-1 in relation to the increase of glucose metabolism of cancer cell, 1 seemed to be weakened by these effects. Note, however, that there was correlation between the expression of GLUT-1 and 18 F-FDG uptake in non-small cancer cells in the lung, colon cancer, and sarcoma 9,18,28 . A few previous studies also reported clinical correlation between glucose metabolism and PET image 13,15,29 .…”
Section: Correlation Between Gss and Histological Diffe Renti Ation mentioning
confidence: 88%
“…That cellular glucose metabolism may be correlated with tumor growth and aggressiveness has been suggested in some studies [17][18][19][20][21] . Previous in vitro and clinical studies indicated an association between elevated FDG uptake and colon tumor glucose metabolism, such as the activity of GLUT1, Ki-67, and p53 [13,[22][23][24][25] . A study by Gu et al [22] indicated that tumor size and depth of invasion were associated with higher SUVs in both primary colon tumors and hepatic metastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and clinical studies indicated an association between elevated FDG uptake and colon tumor glucose metabolism, such as the activity of GLUT1, Ki-67, and p53 [13,[22][23][24][25] . A study by Gu et al [22] indicated that tumor size and depth of invasion were associated with higher SUVs in both primary colon tumors and hepatic metastatic foci. However, the study was limited by a small sample size (20 patients) and survival analysis was not performed.…”
Section: Discussionmentioning
confidence: 99%